Determinan tingkat penggunaan aplikasi non tunai - Rizkina Maharani; Jurana Jurana; Fadli Mohammad Saleh (University of Merdeka Malang, 2023)
Changes in the payment system are developing more rapidly following technological developments, this has caused a change in lifestyle in the behavior of students who used to transact using cash now being replaced by electronic money (e-money). There are several conveniences enjoyed by Tadulako University accounting students as a cashless society, the first of which is more efficient and saves time. As a student, you often don't have much time to eat in the canteen because of the demands of assignments or other academic matters. Waiting for the payment queue is sometimes very time-consuming. With payments using QRIS, it is enough to make payments via scan with the non-cash payment application and enter the nominal payment, the payment will be automatically received by the seller. This research examine the determinant (Lifestyle, Income, and Consumptive Behavior) affecting the level of use of non-cash applications on Tadulako University accounting students. This study's population consisted of all currently enrolled Accounting students—a total of 1,026 students—with a sample size of 293 respondents. The classical assumption is tested first, and the analysis technique employs the Multiple Regression analysis method. Lifestyle has a positive and significant effect, income has a positive and significant effect, and consumption behavior has a positive and significant effect, according to the analysis in this study.